KORELASI ANTARA PENGGUNAAN MEDIA AUDIO DENGAN KETERAMPILAN MENYIMAK CERITA ANAK DI KELAS VA SEKOLAH DASAR NEGERI 17 PONTIANAK KOTA - Janni, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The common problem of this research is there any correlation between usage of audio media with skill of listening to child story in class of VA SD Negeri 17 Pontianak City?â€. This study aims to describe the correlation between the use of audio media with the skills to listen to children's stories in the VA class of Elementary School 17 Pontianak City. Variable in this research consist of independent variable (X) that is use of audio media and dependent variable (Y) that is skill of listening to child story.The method used in this research is descriptive method with research form study relationship. This study is a population study with 36 students. Date collection techniques of indirect communication techniques, direct communication techniques and measurement techniques. The date collection tools used were questionnaires, observations and tests. The results showed that the use of audio media in the class VA State Elementary School 17 Pontianak City belong to the category very good that is equal to 87.22%. While the results of listening skills of children's stories after using the audio media obtained an average value of 75.05 belonging to either category because it entered in the 70-79 value range. There is a moderate relationship between the use of audio media with children's listening skills. This is evidenced by the calculation of correlation coefficient obtained by 0.47. The value is then compared with r table at the 5% level for N = 36 is 0.329. Thus r count> from r table or 0.47> 0.329. In this research alternative Hypothesis (Ha) accepted and Hypothesis zero (H0) rejected because the value of r count is greater than r table, which means there is a correlation / relationship between the use of audio media with the skills to listen to children's story in VA class Elementary School 17 Pontianak City. Keywords: Listening Skills, Child Story, Â Audio Media Â